House Wrens Troglodytes aedon reduce repertoire size and change song element frequencies in response to anthropogenic noise. (9th June 2020) - Juárez, Roselvy; Araya‐Ajoy, Yimen G.; Barrantes, Gilbert; Sandoval, Luis
Abstract : Anthropogenic noise (≤ 3 kHz) can affect key features of birds' acoustic communication via two different processes: (1) song‐learning, because songbirds need to hear themselves and other birds to crystallize their song, and (2) avoidance of song elements that overlap with anthropogenic noise. In this study we tested whether anthropogenic noise reduces the number of song elements in the repertoire of House Wren Troglodytes aedon, an urban species. Additionally, we tested whether the proportion of high‐frequency elements (i.e. elements where the minimum frequency is above 3 kHz) is related to anthropogenic noise levels, and how the frequencies and duration of shared elements between males change with different levels of anthropogenic noise. We recorded 29 House Wren males exposed to different anthropogenic noise levels (36.50–79.50 dB) during two consecutive breeding seasons from four locations. We recorded each male on 2 days during each season continuously for 50 min (we collected 104 h of recordings) and measured anthropogenic noise levels every 10 min inside each male territory during the recording period. In general, individuals inhabiting noisier territories had smaller repertoires. However, only in two locations with anthropogenic noise levels between 38.60 and 79.50 dB did males inhabiting noisier territories have smaller repertoires. In the other two locations with lower anthropogenic noise (36.50–66.50 dB), the anthropogenic noise inside each territory was not related to the repertoire size. Individuals inhabiting the noisiest location showed a tendency to include more high‐frequency elements in their songs. In 26% of the elements, the anthropogenic noise affected their frequency features. Our results showed that not all House Wrens inhabiting urban environments modify their songs at the highest level of organization (i.e. repertoire) to reduce the masking effect of anthropogenic noise on acoustic communication.